THE INFLUENCE OF GROUP WORKS TOWARDS STUDENTS` ABILITY IN WRITING DESCRIPTIVE TEXT AT THE FIRST SEMESTER OF THE SEVENTH CLASS AT SMP BUDI KARYA NATAR LAMPUNG SELATAN IN 2014/2015 - Alfiawati, Riska (Lentera: Jurnal Ilmiah Kependidikan, 2016)
The most important factor in writing is that students need to be personally involved in order to make the learning experience of lasting value. Encouraging students’ participation in the exercise, while at the same time refining and expanding writing skills, requires a certain pragmatic approach. The teacher should be clear on what skills he/she is trying to develop. The method of this research was experimental method. The population of this research was the students at the first semester of the seventh class at SMP Budi Karya Natar Lampung Selatan consisting of 78 students in 2 classes. The samples of this research were two classes, the first class as the experimental class and the second class as control class. In taking the sample, the writer used total sampling technique. In collecting the data, the writer used writing test. The writer provided some topics for the students, and they were asked to write a descriptive text based on the topic chosen. In analyzing the data, the writer used ttest formula. The result of this research showed that the writer proved that the students’ ability in writing descriptive that learn descriptive text was higher than the students’ who learn descriptive through conventional technique. It was proved by the average score of students’ ability in writing descriptive text in experimental class was higher than the average score of students’ ability in writing descriptive text in control class (69.95 > 54.67). Then, the calculation of ttest showed that the score of ttest was higher than ttable with significance level 5% and 1% (7.88>1.67>2.39). Therefore, the writer proved the hypothesis that there is a significant influence of Group Work towards students’ ability in writing descriptive text at the first semester of the seventh class at SMP Budi Karya Natar Lampung Selatan in 2014/2015.